2020
DOI: 10.1101/2020.12.07.414193
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single cell transcriptomics of primate sensory neurons identifies cell types associated with human chronic pain

Abstract: Distinct types of dorsal root ganglion sensory neurons may have unique contributions to chronic pain. Identification of primate sensory neuron types is critical for understanding the cellular origin and heritability of chronic pain. However, molecular insights into the primate sensory neurons are missing. Here we classify non-human primate dorsal root ganglion sensory neurons based on their transcriptome and map human pain heritability to neuronal types. First, we identified cell correlates between two major d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 97 publications
(119 reference statements)
1
12
0
Order By: Relevance
“…A recent study has demonstrated that humans also have Aβ-fiber nociceptors with nociceptive properties (43). The final cluster of A-fibers had high expression of NTRK1 , CPNE6 and SCN10A, which is consistent with Aδ high-threshold mechanoreceptors (HTMRs) in the mouse and macaque (14, 44). This cluster also expressed CALCA and LPAR3 .…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…A recent study has demonstrated that humans also have Aβ-fiber nociceptors with nociceptive properties (43). The final cluster of A-fibers had high expression of NTRK1 , CPNE6 and SCN10A, which is consistent with Aδ high-threshold mechanoreceptors (HTMRs) in the mouse and macaque (14, 44). This cluster also expressed CALCA and LPAR3 .…”
Section: Resultssupporting
confidence: 68%
“…This finding is explained by the expansion of neuronal populations that express HRH1 , the H1 histamine receptor, in human DRG. Interestingly, we do not find expression for most known markers of C-LTMRs in human DRG, including a lack of markers that were recently identified in a nuclear sequencing study from macaques (44), making this population challenging to identify in our study. The exception was GFRA2 expression which marks C-LTMRs across species (16, 23), enabling putative identification of C-LTMRs in human DRG.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In vitro calcium imaging in cultured DRG from DREADD expressing mice confirms that most of the neurons functionally responding to DREADD agonist CNO had a unique C-LTMR chemo response pattern consistent with their transcriptional profile regarding the expression of channels and receptors coupled to cytosolic calcium variations. This includes responses to agonists of TRPA1 agonist as reported before 15,16 , as well as to the purinergic metabotropic receptor P2RY1 that is consistently reported to be highly expressed in C-LTMRs across species from rodents to non-human primates 18,20,42,43 . In addition, the CNO responsive neurons where all negative to live staining with fluorescent IB4, as expected from previous studies 15 .…”
Section: C-ltmrs and Pleasant Touchmentioning
confidence: 98%
“…In humans, classification of primary afferent nociceptors is classically based on their sensory characteristics obtained from single fiber recordings (34)(35)(36)(37)(38), such as mechanical thresholds and temperature sensitivity ( Table 1). Currently, important work is being performed to reduce the translational gaps between rodent and human single cell expression patterns (39,40), but also to link functional characteristics and expression pattern within a single neuron (41). This ongoing work will provide a much more detailed basis for the differentiation between itch and pain processing neurons and the extent of overlap in mediators and receptors.…”
Section: Classic Theories Of Pruritus and Evidence For Interactions Bmentioning
confidence: 99%